Ecotherapy: an alternative therapy for social media addiction during covid-19 outbreak - Putri, Yola Eka; Amalianita, Berru; Ifdil, Ifdil; Zola, Nilma; Fitria, Linda (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
The covid-19 epidemic has led to a major increase in the usage of social media, with many individuals finding sanctuary in the digital realm. In light of the potential for addiction, it has become crucial to develop alternate treatments for social media addiction. Ecotherapy, often known as nature-based therapy, has emerged as a novel and successful treatment for social media addiction among individuals. During the covid-19 epidemic, this essay explores the prospect of ecotherapy as an alternative treatment for social media addiction. In addition, the possible implications of ecotherapy for the treatment of social media addiction during the pandemic will be discussed. This study may serve to guide judgments on the use of ecotherapy during the ongoing epidemic by offering a comprehensive overview of ecotherapy.